Analisis Aliran Cetakan Paving Block Menggunakan Material Polypropylene (PP) - Yoga Aryatama; Muhammad Yunus; Subkhan Subkhan (Jurnal Inovasi Teknologi Terapan, 2026)
This study presents the design and flow analysis of a polypropylene (PP) injection mold for paving block production as a cost-efficient and lightweight alternative to conventional metal molds. The research consists of a field survey at Tacon company, product geometry evaluation, mold design using SolidWorks, and flow simulation to assess mold performance. Simulation results indicate that the two-plate mold with a 2 mm wall thickness can withstand loads up to two stacked paving blocks (40 N) without deformation. The filling time was recorded at 1.6491 seconds, with a maximum injection pressure of 49.03 MPa, and cooling time ranging between 5.14–10.64 seconds. The sink mark value was very small (0.0031 mm) and located in non-critical areas, while air traps appeared only at the cavity edges. These findings confirm that PP can be effectively used as a mold material for paving blocks, providing stable melt flow behavior, good product quality, and efficient cooling cycles. This research contributes to the development of polymer-based mold technology for affordable, lightweight, and locally manufacturable paving block production.